A review on bismuth oxyhalide based materials for photocatalysis. Issue 12 (21st May 2021) - Wei, Xuejiao; Akbar, Muhammad Usama; Raza, Ali; Li, Gao
Abstract : A new class of photocatalysts comprising ternary semiconductors such as BiOX joined via van der Waals forces is potential candidates for photocatalysis because of their high charge transfer ratio due to their indirect band gaps with crystallinity. Abstract : Photocatalytic solar energy transformation is the most encouraging solution to alleviate the environmental crisis and energy scarcity. Bismuth oxyhalide (BiOX) is an emerging class of materials that exhibits photocatalytic properties, such as resilient response to light, which causes enhanced energy conversion (solar energy) owing to their exceptional layered structure and attractive band structure. The present review presents a summary of results from the recent developments on the tuning and design of BiOX-based materials to improve the energy conversion. In particular, the preparation and tuning approaches that have the potential to enhance the photocatalytic behavior of BiOX and some other techniques, such as elemental doping, are addressed, which prevent the rapid recombination of charges, and formation of oxygen vacancies, facilitating an improvement in the photocatalytic reaction. Various frameworks are also presented, displaying the significance of BiOX-based nanocomposites. Finally, the main challenges and opportunities associated with the future progress of BiOX-based materials are presented. This review will provide an extended understanding and offer a preferred direction for the innovative design of BiOX-based materials for environmental and especially energy-based applications.